2016
DOI: 10.3389/fpsyt.2016.00008
|View full text |Cite
|
Sign up to set email alerts
|

The Addictive Model of Self-Harming (Non-suicidal and Suicidal) Behavior

Abstract: IntroductionBehavioral addictions such as gambling, sun-tanning, shopping, Internet use, work, exercise, or even love and sex are frequent, and share many characteristics and common neurobiological and genetic underpinnings with substance addictions (i.e., tolerance, withdrawal, and relapse). Recent literature suggests that both non-suicidal self-injury (NSSI) and suicidal behavior (SB) can also be conceptualized as addictions. The major aim of this mini review is to review the literature and explore the neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(77 citation statements)
references
References 77 publications
3
61
0
13
Order By: Relevance
“…However, it is important to note that the measures of impulsivity in these studies were not directly related to engagement of self-harm, unlike the question in our study. Recent literature has also suggested that repetitive self-harm could be considered as an addictive behavior [43]. Based on this notion, it can be suggested that these individuals are dealing with strong urges to harm themselves.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that the measures of impulsivity in these studies were not directly related to engagement of self-harm, unlike the question in our study. Recent literature has also suggested that repetitive self-harm could be considered as an addictive behavior [43]. Based on this notion, it can be suggested that these individuals are dealing with strong urges to harm themselves.…”
Section: Discussionmentioning
confidence: 99%
“…The addiction to self‐harming behaviours can be explained either by neurobiological or by psychological mechanisms. Concerning neurobiological mechanisms, opioid and dopaminergic systems, and hypothalamo–pituitary–adrenal (HPA) axis, which interact in the forebrain can be activated either by psychoactive drugs or by behaviours, are probably involved in the development of an addiction to suicidal behaviours . For psychological mechanisms, previous suicidal behaviour sensitizes suicidal thoughts and behaviours, such that they become more autonomous and easily precipitated .…”
Section: Discussionmentioning
confidence: 99%
“…Becoming more easily triggered by stressful life events, suicidal behaviours also become more persistent and severe. The cathartic effect might be explained by either mobilization of interpersonal support (i.e., medical attention, caring family) or emotional venting of an unbearable emotional or physical state (experiential avoidance from mental pain) . Besides, past suicidal experience, especially if severe, affects subsequent suicidal symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Динаміка ЧРСС заднього вентролатерального гіпоталамуса у щурів із високим рівнем потреби в позитивному емоційному підкріпленні: а -ЧРСС вентролатерального гіпоталамуса щурів з її вірогідним підвищенням; б -ЧРСС вентролатерального гіпоталамуса (загальна група); в -ЧРСС вентролатерального гіпоталамуса щурів без її вірогідного підвищення У стані відміни самостимуляції вентролатерального гіпоталамуса емоційна поведінка щурів була різноманітною. В одних тварин формувалися реакції агресивної спрямованості: підвищена рухова активність із судомними обтрушуваннями, скрегіт зубів, негативний грумінг, що підтверджується літературними даними (Ferguson, 2015;Zinkiewicz, 2015;Blasco-Fontecilla, 2016). В інших формувалися реакції тривожно-фобічної спрямованості: реакції страху, тварини забивалися в куток клітки, що супроводжувалося сильним вегетативним забезпеченням, численними актами дефекації та сечовипускання; відзначалося зниження рухової активності, зростання внутрішньої напруги.…”
Section: результатиunclassified